Ecological methods of assessing the quality of the environment in the fluctuating asymmetry of birch leaves - Matveevich Mazurkin, Peter (Discoveries in Agriculture and Food Sciences, 2018)
The methods of ecological assessment of the environmental quality of growing birch trees on fluctuating asymmetry of leaves after their stop in growth are briefly presented. In comparison with the average values of parameter measurements, each of the five leaves from at least three birches improves the accuracy of modeling and seven times reduces the complexity of measurements.